AN INVESTIGATION INTO INTERNATIONAL STUDENTS’ EXPERIENCES AT A VIETNAMESE UNIVERSITY (Journal of Foreign Language Studies, 2024)
This study investigates the experiences of international students during their studies at a university in Vietnam. Adopting the Sociocultural Adaptation Scale (SCAS) by Ward and Kennedy (1999), the study attempts to explore the effects of different aspects of a new environment on international students’ overall adaptation while studying in Vietnam. The results reveal that successful adaptation to university life had the strongest effect, followed by basic needs as well as objective and subjective obstacles, while social aspects exerted the weakest impact. International students had few difficulties in learning Vietnamese, but it took them some time to adapt to some social and cultural phenomena. This study offers some suggestions for international students and host universities in their internationalization endeavors.
Keywords: international students; Sociocultural Adaptation Scale (SCAS); university life; internationalization